(untitled) (Farabi Journal of Social Sciences, 2019)
Abstract. The bases of national tax systems should be considered depending on the state of the economic and sociopolitical structure in the conditions of market reforms. Thus, the special place in creating a tax systemof market type are the principles of its construction. If under the tax system the totality of taxes considered, duties and charges levied on the territory of the state in accordance with the Tax code, and a set of rules and regulations that define the authority and responsibility of the parties involved in tax transactions. In addition, particularly the importance of practicing the principles of the tax system in relation to the characteristics of the development of the state. The emergence of a fundamentally different model of interaction between government and business entities in the field of taxation has determined the necessity for consideration of the tax component in the total economic strategy of the enterprises. In this regard, there is a need of economic agents in the formation of individual tax policies that address issues the optimization of tax burden. However, despite the urgency of research influenceof the tax.